2016
DOI: 10.4049/jimmunol.1600902
|View full text |Cite
|
Sign up to set email alerts
|

TLR8 Couples SOCS-1 and Restrains TLR7-Mediated Antiviral Immunity, Exacerbating West Nile Virus Infection in Mice

Abstract: West Nile virus (WNV) is a neurotropic, single-stranded RNA (ssRNA) flavivirus that can cause encephalitis, meningitis, and death in humans and mice. Human Toll-like receptor (TLR) 7, 8, and mouse TLR7 recognize viral ssRNA motifs and induce antiviral immunity. However, the role of mouse TLR8 in antiviral immunity is poorly understood. Here, we report that TLR8 deficient (Tlr8−/−) mice were resistant to WNV infection compared to wild-type (WT) controls. Efficient WNV clearance and moderate susceptibility to WN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 91 publications
0
14
0
Order By: Relevance
“…Human TLR8 can recognize viral ssRNA, but mouse TLR8 was described as nonfunctional, which may be due to a deletion of 5 amino acids in the leucine-rich repeat ectodomain of TLR8 in mice [42]. Although TLR8 may not directly sense WNV RNA, it interacts with suppressor of cytokine signaling (SOCS)-1 and restrains TLR7 mediated antiviral immunity in mice [43].…”
Section: Innate Immunitymentioning
confidence: 99%
“…Human TLR8 can recognize viral ssRNA, but mouse TLR8 was described as nonfunctional, which may be due to a deletion of 5 amino acids in the leucine-rich repeat ectodomain of TLR8 in mice [42]. Although TLR8 may not directly sense WNV RNA, it interacts with suppressor of cytokine signaling (SOCS)-1 and restrains TLR7 mediated antiviral immunity in mice [43].…”
Section: Innate Immunitymentioning
confidence: 99%
“…First, the clinical data provide evidence that WNV infection in humans induces a significant upregulation of TNF-α. This is not surprising since previous studies in mice and cell cultures have demonstrated essential protective roles for TNF-α and other proinflammatory cytokines against acute WNV infection (10,(12)(13)(14) Moreover, high TNF-α levels have been reported in other flavivirus human infections, including dengue (21,22), Zika virus (23,24), and Japanese encephalitis virus (JEV) (25). Children infected with dengue virus showed significantly higher serum levels of TNF-α, with the highest levels in those with severe dengue disease (21), formerly "dengue shock syndrome" and "dengue hemorrhagic fever."…”
Section: Discussionmentioning
confidence: 86%
“…On a molecular level, acute WNV infection induces a significant upregulation of various proinflammatory proteins, including astroglial protein S100B and the receptor for advanced glycation end products (RAGE) (7), high-mobility group box-1 (HMGB1) (8), and osteopontin (OPN) (9), which initiate and maintain an inflammatory cascade that increases production of pro-inflammatory cytokines, interleukins (ILs), and chemokines (10)(11)(12) as part of the initial antiviral immune response. Previous studies in mice and cell cultures have demonstrated essential protective roles for these proinflammatory proteins against acute WNV infection (13,14). However, these antiviral molecules have also been reported to persist for months following the acute illness, leading to a post-infectious proinflammatory state that may contribute to long-term neuroinflammation and cytotoxicity in some WNV survivors (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Our study indicated that the virus-induced increase in SOCS1 expression in primary macrophages was mediated by TLR3 and NF-κB activation. Both TLRs [ 46 ] and NF-κB [ 47 , 48 ] have been reported to be regulators of SOCS1 expression. In addition to MHV-68 infection, we demonstrated that when TLR3 on BMMs was activated by poly(I:C), the SOCS1 expression was also induced ( Fig 6B ) in a manner dependent on NF-κB activation ( Fig 7D ).…”
Section: Discussionmentioning
confidence: 99%